2010
DOI: 10.1002/pola.24246
|View full text |Cite
|
Sign up to set email alerts
|

A new room‐temperature liquid, high‐performance tricyanate ester

Abstract: A new tricyanate ester monomer of a tris(4‐hydroxyphenyl)benzene derivative was synthesized in 6‐steps with a 63% overall yield. The geminal substitution of phenyl rings on ethane, in addition to the creation of a racemic/diastereomeric mixture, resulted in a liquid monomer whereas compounds with similar structure and symmetry have melting points typically over 100 °C. Key properties of the polycyanurate, such as the glass transition temperature and moisture resistance, were positively influenced by the higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 30 publications
(21 reference statements)
0
16
0
Order By: Relevance
“…In addition, FTIR analysis of the polycyanurate after 280 °C “post‐cure” show that the cyanate ester peak found at 2250 cm −1 had all but disappeared and the typical strong bands associated with cyanurate ring at 1360 and 1560 cm −1 had appeared, Figure …”
Section: Resultsmentioning
confidence: 98%
“…In addition, FTIR analysis of the polycyanurate after 280 °C “post‐cure” show that the cyanate ester peak found at 2250 cm −1 had all but disappeared and the typical strong bands associated with cyanurate ring at 1360 and 1560 cm −1 had appeared, Figure …”
Section: Resultsmentioning
confidence: 98%
“…The 1,1-di- 208 www.chemsuschem.org phenylethane framework typically results in depressed melting points compared to methylene or 2,2-diphenylpropane linkages. [19] Despite this discrepancy, the melting point exhibited a drastic decrease upon extension of the reaction from acetaldehyde to propionaldehyde, and 5 was isolated as a viscous oil. For applications as precursors to thermosetting composites, lower melting resins should allow simplified and lower-cost fabrication methods.…”
Section: Structures and Properties Of Bisphenolsmentioning
confidence: 99%
“…Snow and coworkers prepared oligodimethylsiloxanes linked cyanate esters with low dielectric characteristic 4. Davis and coworkers used racemic/diastereomeric concept to prepare a liquid‐type tricyanate ester for favorable processing characteristic and enhanced thermomechanical performance in wet environments 5. Wang and coworkers prepared phenolphthalein‐based cyanate esters with high‐ T g for higher temperature applications 6.…”
Section: Introductionmentioning
confidence: 99%
“…Although poly(cyanate esters) display promising properties, the lack of flame retardancy is a drawback of cyanate ester for electronic applications, where meeting a flame retardancy standard, UL‐94 V‐0, is required. Literatures have reported that the flame retardancy of cyanate esters can be greatly enhanced by the incorporation of phosphorus element 5, 9–18…”
Section: Introductionmentioning
confidence: 99%